Der 32P-Test zur Diagnose intraokulärer Melanome – eine obsolete Untersuchungs methode? - Beck, B.; von Kügelgen, O.; Jung, B.; Heinze, H. G.; Müller-Jensen, K. (Nuklearmedizin - NuclearMedicine, 1991)
Results of the 32P uptake test for the diagnosis of chorioideal melanoma in 41 patients are reported. The sensitivity was 80%, the specifity 86%, if a count rate ratio of more than 1.4 between tumor and normal tissue was considered as pathological. Ratios between 1.4 and 1.6 ought to be considered as equivocal in which case specifity increases to 90%. The 32P uptake test still remains a method of clinical relevance in the diagnosis of chorioideal melanoma.